Sirolimus in the Treatment of Vascular Anomalies - Triana, Paloma; Dore, Mariela; Cerezo, Vanesa Nuñez; Cervantes, Manuel; Sánchez, Alejandra Vilanova; Ferrero, Miriam Miguel; González, Mercedes Díaz; Lopez-Gutierrez, Juan Carlos (European Journal of Pediatric Surgery, 2017)
Aim of the Study mTOR inhibitors are showing promising results in the management of vascular anomalies. Although current controlled trials remain to be completed, many individual experiences are being published. We present our series of children with complex vascular anomalies treated with sirolimus.Patients and Methods A retrospective review of 41 patients treated with sirolimus between January 2011 and December 2015 was performed: 15% (n = 6) had vascular tumors (4 kaposiform hemangioendotheliomas, 1 PTEN) and 85% (n = 35) had malformations (13 generalized lymphatic anomalies/Gorham–Stout diseases [GSD], 1 kaposiform lymphangiomatosis [KLA], 11 large lymphatic malformations (LMs) in critical areas, 2 lymphedemas, 4 venous malformations, and 4 aggressive arteriovenous malformations [AVM]). Several variables were collected: type of vascular anomaly, duration of treatment, dosage, response, and secondary effects.Results There was a female predominance (1.4:1). All patients received sirolimus, at initial dosage of 0.8 mg/m2/12 hour. Overall successful response rate was 80.4% of cases, presenting improvement in radiologic imaging and reduction of symptoms, at a median time of 10 weeks. Patients showing no response included four AVMs, one GSD, one LM, one KLA, and one unknown tumor. Sirolimus was well tolerated, even in neonates, with insignificant side effects. No patients had complete resolution and no patients worsened on therapy. Thirty patients remain under treatment at the present moment.Conclusion Sirolimus has become a new therapeutic option for patients with vascular anomalies that do not respond to other treatments. Unfortunately, important questions as what is the most appropriate dosage and for how long should the patient be treated remain unanswered. An international registry followed by customized controlled trials is mandatory to clarify the future of this therapy.
Keywords: vascular anomalies; sirolimus; mTOR inhibitors; pediatrics